Evaluation of the bond strength of chlorhexidine incorporated into the adhesive system composition: A PRISMA guided meta-analysis - Xue Zhang; Lina Wang; Shuo Liu; Hua Bai; Weidong Niu (Elsevier, 2020)
Background/purpose: Composite resin is currently the most widely used dental restoration material. Previous studies have demonstrated that the application of Chlorhexidine (CHX) on the dentin surface after acid etching can result in an improvement in the integrity and stability of tooth restoration through time. In order to better understand whether CHX can help improve the stability of the resin-dentin bond strength, in this study, a comprehensive review of the effect of adding CHX to the adhesive system on the stability of immediate and long-term resin-dentin bond strength was conducted. Materials and methods: This article was written in accordance with the PRISMA Statement and is registered on the International Prospective Register of Systematic Reviews (registration number CRD42018084962). Six electronic databases including PubMed, Embase, Cochrane library, ISI Web of Science, ClinicalTrials.gov and China National Knowledge Infrastructure (CNKI) were searched up to October, 2018. Ten articles were selected from 340 possible eligible articles for meta-analysis, and 41 sets of data were analyzed in the meta-analysis. Results: The results indicated that the use of 0.1% and 0.2% CHX does not adversely affect the immediate bond strength (p > 0.05), but both 0.1% and 0.2% CHX increased bond strength compared with the control group over 12 months (p < 0.05). However, this trend does not represent a longer period of aging. Conclusion: In these in vitro clinical trials, CHX incorporated into the bonding systems maintained the stability of bond strength.